2021
DOI: 10.1016/j.jcis.2020.08.117
|View full text |Cite
|
Sign up to set email alerts
|

Ruthenium tris(2,2′-bipyridyl) complex encapsulated in nanosized faujasite zeolite as intracellular localization tracer

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…29,30 Furthermore, an absorption spectrum (Figure 2b) was collected for Ru(bpy) 3 2+ containing an absorption band with a maximum at 451 nm, which is attributed to the metal-to-ligand charge transfer (MLCT) from the d-orbital of Ru to the π*-orbital of the bipyridine ligand. 30,31 The EMC-1-Ru, measured in diffuse reflectance mode, had a similar absorption pattern with a maximum at 453 nm, leading to the excitation of the photocatalyst in the visible-light region. Additionally, band gap calculations (via the Kubelka−Munk theory) from the UV−Vis data indicated that the HOMO−LUMO gap of the Ru-loaded material (2.6 eV) is in line with the MLCT of the homogeneous complex (Figure S6).…”
Section: ■ Results and Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…29,30 Furthermore, an absorption spectrum (Figure 2b) was collected for Ru(bpy) 3 2+ containing an absorption band with a maximum at 451 nm, which is attributed to the metal-to-ligand charge transfer (MLCT) from the d-orbital of Ru to the π*-orbital of the bipyridine ligand. 30,31 The EMC-1-Ru, measured in diffuse reflectance mode, had a similar absorption pattern with a maximum at 453 nm, leading to the excitation of the photocatalyst in the visible-light region. Additionally, band gap calculations (via the Kubelka−Munk theory) from the UV−Vis data indicated that the HOMO−LUMO gap of the Ru-loaded material (2.6 eV) is in line with the MLCT of the homogeneous complex (Figure S6).…”
Section: ■ Results and Discussionmentioning
confidence: 95%
“…Fourier-transform infrared spectroscopy (FTIR) data confirmed the presence of Ru(bipy) 3 2+ based on the characteristic bands in the region 1400 to 1500 cm −1 , which are associated to the C−C and C−N stretch vibrations and/or the C−H in-plane bend of the 2,2′-bipyridine ligand (Figure S5). 29,30 Furthermore, an absorption spectrum (Figure 2b) was collected for Ru(bpy) 3 2+ containing an absorption band with a maximum at 451 nm, which is attributed to the metal-to-ligand charge transfer (MLCT) from the d-orbital of Ru to the π*-orbital of the bipyridine ligand. 30,31 The EMC-1-Ru, measured in diffuse reflectance mode, had a similar absorption pattern with a maximum at 453 nm, leading to the excitation of the photocatalyst in the visible-light region.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The nanosized FAU zeolite containing ruthenium complex (Ru(bpy)3-FAU) was used as a solid and as a colloidal suspension in double distilled water; the Ru(bpy)3-FAU was prepared according to the method reported by our group [13].…”
Section: Synthesis Of Nanosized Zeolitesmentioning
confidence: 99%
“…The samples exhibit high external surface area of 785 and 685 m 2 /g for Na-FAU-X and Gd-FAU-X, respectively. The characterization of sample Ru(bpy)3-FAU-X can be found in our recent article [13].…”
Section: Characterization Of Nanosized Fau-based Zeolitesmentioning
confidence: 99%
See 1 more Smart Citation